Nourrir les morts ou « Celui qui fait vivre », les différents régimes de commensalité rituelle chez les Mixe (Oaxaca, Mexique) - Perig Pitrou (Journal de la Société des Américanistes)
The public and private celebrations that take place in Mexico in connection with the Day of the Dead (Día de Muertos), as well as the many representations of death in the form of the Catrina and skeletons, are part of a popular culture that extends well beyond the country’s borders. The development of this imaginary, in particular in urban areas, supports the idea that Mexicans maintain close relations with the dead, whom they welcome with meals in the festive atmosphere that marks their yearly return. However, ethnographic observation of alimentary transfers realized for these visitors and performed by Mixe communities in the state of Oaxaca proves that the principle of expelling the dead out of the domestic sphere is not forgotten during the Day of the Dead. To demonstrate this, this article proposes a contrastive study between systems of meal-sharing associated with ceremonial deposits – poultry sacrifices – on the basis of whether these displays are intended for the dead or, instead, for an entity named « The One Who Makes Live ». Whereas the anthropology of religion has often studied the symbolism of the elements transferred during ritual food offerings, the angle of analysis I use here focuses on the interactional dynamics through which the acceptance of such an offering may be staged by these recipients. By focusing on this, it becomes clear that in spite of similarities between the forms of these rituals, there are profound differences in the relations to both types of recipients as well as to the kinds of agency attributed to each of them.